Molecular diagnostic techniques in respiratory infections - Jordi Vila-Estapé; Arturo Martínez-Trejo; Giulia Gatti; Natalia Roson-Calero; Laia Fernandez-Barat; Antoni Torres; Andrea Vergara-Gómez (Barcelona Respiratory Network Reviews)
The diagnosis of community-acquired pneumonia and hospital-acquired pneumonia is based on clinical, radiological, and microbiological findings. Conventional methods are based on the culture of respiratory samples, including sputum, endotracheal aspirate, bronchoaspirate, and bronchoalveolar lavage, followed by strain identification and antibiotic susceptibility testing. The gold standard for microbiological diagnosis of pneumonia remains the culture-based methods. These take > 24 h to identify the bacteria and 48 h to provide antibacterial susceptibility. Culture is insensitive, only detecting a pathogen in 23-40% of patients with clinically diagnosed pneumonia and an even smaller proportion after the administration of antibiotics. The utilization of multiplex panels for the simultaneous detection and identification of respiratory pathogens, including the detection of resistant determinants, can streamline testing procedures and enhance both the sensitivity and speed of diagnosis compared to traditional. In this review, molecular testing is currently available, and the potential future applications of next-generation sequencing are developed.